2017
DOI: 10.1002/hbm.23884
|View full text |Cite
|
Sign up to set email alerts
|

Brain networks of the imaginative mind: Dynamic functional connectivity of default and cognitive control networks relates to openness to experience

Abstract: Imagination and creative cognition are often associated with the brain's default network (DN). Recent evidence has also linked cognitive control systems to performance on tasks involving imagination and creativity, with a growing number of studies reporting functional interactions between cognitive control and DN regions. We sought to extend the emerging literature on brain dynamics supporting imagination by examining individual differences in large-scale network connectivity in relation to Openness to Experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 79 publications
(150 reference statements)
4
63
1
2
Order By: Relevance
“…For instance, others have found that openness predicted the global efficiency of a functional network comprised of DMN nodes, and, similar to our findings, this result remained significant after controlling for intelligence, age, sex, and other personality variables (Beaty et al, ). In addition, openness has been found to be positively associated with functional connectivity between DMN hubs and regions and networks associated with cognitive control (Adelstein et al, ; Beaty et al, ). Given the fact that people with higher openness/intellect tend to be imaginative, curious, innovative, and creative (Allen & DeYoung, ), we expected that the DMN would be a relevant substrate of this trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, others have found that openness predicted the global efficiency of a functional network comprised of DMN nodes, and, similar to our findings, this result remained significant after controlling for intelligence, age, sex, and other personality variables (Beaty et al, ). In addition, openness has been found to be positively associated with functional connectivity between DMN hubs and regions and networks associated with cognitive control (Adelstein et al, ; Beaty et al, ). Given the fact that people with higher openness/intellect tend to be imaginative, curious, innovative, and creative (Allen & DeYoung, ), we expected that the DMN would be a relevant substrate of this trait.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding openness/intellect, is suggested that DMN play a relevant role given it implications on imagination, imagery, and creativity (Allen & DeYoung, ; Beaty et al, ). For instance, higher levels of openness/intellect were associated with higher FC between DMN and regions or networks associated with cognitive control (Adelstein et al, ; Beaty et al, ), and predicted global efficiency of a network comprised of DMN nodes (Beaty et al, ). In relation to conscientiousness, FPN and VAN have been considered good candidates for a neural substrate since they are relevant to reorienting attention away from distractions and toward stimuli important for goal pursuit (Allen & DeYoung, ).…”
Section: Introductionmentioning
confidence: 99%
“…These parameters can then be probed for association with measures of inter-or intra-individual differences (e.g. (Beaty, et al 2018;Marusak, et al 2018;Vidaurre, et al 2017b)). State-based approaches can differ in whether they assume smooth transitions between states (Allen, et al 2014;Ou, et al 2015) or instantaneous reconfigurations Yaesoubi, et al 2018), their focus on a particular signal domain (e.g.…”
Section: Example 1: Data-driven Models Of Tvcmentioning
confidence: 99%
“…Neuroimaging techniques are widely used to estimate the brain cortical networks involved in the normal brain cognitive functions as well as in neurological diseases [1-6]. Diffusion Tensor Imaging (DTI) can be adapted to estimate SC with higher capability [7-9].…”
Section: Introductionmentioning
confidence: 99%